2009
DOI: 10.4103/0019-509x.48594
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of bone marrow histology in multiple myeloma

Abstract: BACKGROUND: Bone marrow examination continues to be the cornerstone for establishing the diagnosis of multiple myeloma in association with other clinical and laboratory parameters. Plasma cell morphology has signifi cant correlation with clinical stage and survival. AIMS: To note the bone marrow histology in detail in multiple myeloma and to correlate it with clinical stage and survival. METHODS AND MATERIAL: Fifty-fi ve cases of multiple myeloma diagnosed between January 2001 and December 2006, who had a bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
26
3
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 13 publications
10
26
3
3
Order By: Relevance
“…[16] We also observed only one patient less than 40 years. The mean age of presentation was 58.38 years which is in accordance with other studies [4][5][6][7]15] whereas it is lower than that observed by Diwan G et al (62 years) [14] and Rajkumar S.V. (65 years).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[16] We also observed only one patient less than 40 years. The mean age of presentation was 58.38 years which is in accordance with other studies [4][5][6][7]15] whereas it is lower than that observed by Diwan G et al (62 years) [14] and Rajkumar S.V. (65 years).…”
Section: Discussionsupporting
confidence: 89%
“…Multiple myeloma (MM) is a disease predominantly of middle aged and elderly. [1] The median age of presentation in India is a decade lesser around 55 -62 years [4][5][6][7] in comparison to Western countries. [1,8] Incidence increases with age and the disease has slight male predilection.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable presenting complaints DOI:http://dx.doi.org/10.7314/APJCP.2016.17.4.1833 were observed by prior Pakistani and USA studies, detected fatigue and backaches in 78% and 80% respectively (Shaheen et al, 1999;Kyle et al, 2003). Bony pains and easy fatigability were also the most common symptoms in another study reported from India by Subramanian (Subramanian et al, 2009).…”
Section: Discussionmentioning
confidence: 58%
“…A study by Subramanian et al showed significant correlation between poorly differentiated plasma cell morphology and increased plasma cell burden in the marrow. 8 In our study even though cross-tabulation suggested significant relation between morphology and stage, statistical significance could not be proven due to the limited sample size of 100 cases.…”
Section: Discussionmentioning
confidence: 56%